Penerapan metode bernyanyi islami dalam meningkatkan kemampuan bahasa anak usia dini - dari, eka sari wulan (Maliki Interdisciplinary Journal, 2025)
Language development is an important aspect in the growth and development of early childhood, because through language children learn to express their thoughts, feelings, and desires. In Islamic Early Childhood Education (PAUD) institutions, language development is not only focused on the technical aspects of communication, but is also linked to the instillation of Islamic values ​​from an early age. One method that has proven to be fun and effective in supporting this is through Islamic singing activities. Songs with an Islamic nuance, such as daily prayers, the names of the Prophets, Asmaul Husna, and songs of noble morals, contain word and sentence arrangements that are easy for children to imitate. Through repetition of lyrics, interesting rhythms, and a combination of movement and expression, children absorb new vocabulary more quickly and dare to express simple sentences. Singing also creates a fun learning atmosphere, so that children participate more actively. Islamic songs indirectly help children understand basic concepts in the Islamic religion, while improving their listening, imitating, and speaking abilities and are able to encourage children’s language and motor skills. Therefore, the Islamic singing method can be used as an alternative strategy for developing language that is not only educational, but also spiritual. PAUD teachers need to integrate this method into daily learning to help the process of developing children’s language optimally and meaningfully. And the singing method is used so that children can understand Islamic songs and can encourage children’s language creativity.